A year away to 100th year of vitamin E synthesis. (17th June 2021) - Kundu, Subhradip; Sarkar, Debayan
Abstract: Vitamin E was discovered in the year 1922 as a dietary constituent by Herbert McLean Evans and Katharine J. Scott Bishop. Next year we will be celebrating 100th year anniversary of vitamin E discovery. This minireview highlights discoveries of eight naturally available forms (tocopherols and tocotrienols) of vitamin E and their most important synthetic attempts. This minireview is dedicated to the pioneers of vitamin E for serving a crucial biomolecule to the mankind. Abstract :